Islamic finance for dummies - Jamaldeen, Faleel; Friedman, Joan (For dummies, 2012)
A detailed look at the fast-growing Islamic banking and finance sector. Understand how Islamic financial firms develop products; grasp the objectives and sources of Islamic law and the basic guidelines for business contracts; Learn about Islamic fund management, sukuk, and insurance, and much more